KOLABORASI APOTEKER DENGAN MULTIDISIPLIN ILMU DALAM PENGGUNAAN OBAT DAN EDUKASI PHBS DI LOKASI PENGUNGSIAN GEMPA BUMI CIANJUR - Hermanus Ehe Hurit; Syurya Muhammad Nur; Sri Teguh Rahayu; Tyas Putri Utami; Robby Rijal Sauri; Muhammat Khairun Nafa; Agung Setiawan; Miftahul Ilmy Setiawan; Muh Dewa Putra (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Earthquakes that often occur give rise to social problems such as property damage, loss of life, poverty, hunger, and people who are sick, both from illness and injuries due to collapses and stress due to prolonged trauma. The earthquake that occurred in Cianjur, West Java in November 2022 had a broad impact on the local community. A team of volunteers from Esa Unggul University consisting of multidisciplinary sciences who collaborated to be part of handling post-earthquake problems through basic health services and educating the public about Clean and Healthy Behavior (PHBS), to prevent diseases that will appear after the earthquake. This community service activity was carried out in the villages of Ciputri and Ciherang, Pacet District, Cianjur Regency, West Java, which is about 2 km from the epicenter of the earthquake. The method used was providing health services to earthquake victims at evacuation sites and educating them about Clean and Healthy Behavior (PHBS). The results obtained after providing PHBS health and education services were seen from the reduction in disease outbreaks that emerged after the earthquake and only three types of diseases, namely diarrhea 3%, acute respiratory infection 9.36% and allergic rhinitis 13.48% ten days after the earthquake. This community service activity can increase public awareness in preventing various diseases that arise after the earthquake